Joint Pricing and Inventory Control under Reference Price Effects - Gimpl-Heersink, Lisa; Ohio Library and Information Network (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2018)
In this work, we address the problem of simultaneously determining a pricing and inventory replenishment strategy under reference price effects. This reference price effect models the fact that consumers not only react sensitively to the current price, but also to deviations from a reference price formed on the basis of past purchases. Immediate effects of price reductions on profits have to be weighted against the resulting losses in future periods. By providing an analytical analysis and numerical simulations we study how the additional dynamics of the consumers' willingness to pay affect an optimal pricing and inventory control model and whether a simple policy such as a base-stock-list-price policy holds in such a setting
Inventory Management -- Pricing -- Reference Price -- Stochastic Demand Model -- Dynamic Programming -- Demand Behaviour -- Models in Operations Research Literature -- Models in Marketing Literature -- Integrated Model with Reference Price Effects -- Numerical Simulations -- Analytical Analysis
Thesis (Doctoral)
Keywords: Pricing -- Mathematical models; Inventory control -- Mathematical models; Electronic books; Academic theses